Case report Leukoencephalopathy with vanishing white matter due to homozygous EIF2B2 gene mutation. First Polish cases - Mierzewska, Hanna; van der Knaap, Marjo S.; Scheper, Gert C.; Jurkiewicz, Elżbieta; Schmidt-Sidor, Bogna; Szymańska, Krystyna (Folia Neuropathologica, 2006)
Leukoencephalopathy with vanishing white matter (VWM), also called childhood ataxia with central nervous system hypomyelination (CACH), is an autosomal recessive disease caused by mutations in any of the five genes encoding subunits of the eukaryotic translation initiation factor eIF2B. Neuropathological findings comprise a severe, cavitating orthochromatic leukodystrophy with only small amounts of myelin breakdown products, and predominantly involving the cerebral hemispheric white matter. Within the white matter abnormal oligodendroglial cells are present with abundant “foamy” cytoplasm. In some regions oligodendroglial cells are increased in numbers. We present three sisters, 18, 11 and 8 years old, with the early to late childhood phenotype. The first signs of the disease were gait disturbances at 4, 2 and 6 years of age, respectively. Neurological examination showed mild tremor of hands and head, truncal ataxia, dysarthria, and hypotonia, after several years followed by spasticity. The course of the disease was slowly progressive. Intellectual abilities are relatively spared. The MRI showed diffusely abnormal white matter of the cerebral hemispheres. The FLAIR images revealed rarefaction of the affected white matter with some stripe-like structures, suggesting the presence of remaining tissue strands. The abnormalities were most pronounced with the middle sister, who had the earliest onset of the disease. A homozygous point mutation in the EIF2B2 gene was found, 638A>G. Both the parents were found to be carriers of this mutation. This is the first description of a Polish family with VWM.